PARASITOIDS (HYMENOPTERA: CHALCIDOIDEA) OF THE SEED EATER WEEVIL, OXYSTOMA OCHROPUS (GERMAR) (COLEOPTERA: APIONIDAE) IN NORTHWESTERN IRAN (Acta Entomologica Serbica, 2015)
To study Oxystoma ochropus (Germar, 1818) parasitoids on grass pea (Lathyrus sativus), weekly sampling was done inNamin, Ardabil Province, Iran, during 2011, and samples were transferred to laboratory conditions. In this study, fourparasitic wasps of three chalcidoid families were determined. These parasitoids were Eupelmus microzonus Förster,1860 (Eupelmidae), Eurytoma laserpitii Mayr, 1878 (Eurytomidae), Pteromalus chlorospilus (Walker, 1834) andPteromalus sequester Walker, 1835 (Pteromalidae). The species P. chlorospilus is a new record for Iranian fauna. Inaddition, all established trophic associations of the analyzed parasitoids with O. ochropus as their host are new for theinvestigated territory.